Diet and sleep health: a scoping review of intervention studies in adults. Issue 3 (27th January 2020) - Burrows, T.; Fenton, S.; Duncan, M.
Abstract: Background: Recent research has demonstrated an association between dietary intake and sleep health that can influence chronic disease risk factors. A scoping review of research studies investigating dietary intake and sleep was undertaken to determine the extent and scope of research in laboratory‐based, free‐living and mixed settings. Additionally, this review determines how well subpopulations and geographical locations are represented and the methodologies used to assess outcome measures. Methods: Five online databases were used to identify papers published between 1970 and 2017. Included studies were those conducted in adults and reported both outcomes of interest: (i) sleep health, including sleep restriction and sleep hygiene and (ii) dietary outcomes, including altered nutrients, dietary patterns and supplements. Results: In total, 129 publications were included with the majority being dietary interventions investigating sleep outcomes ( n  = 109) with fewer being sleep interventions investigating and reporting dietary outcomes ( n  = 20). Dietary interventions were most often carried out in free‐living environments, in contrast to sleep interventions that were most often carried out in laboratory‐based environments. The majority of dietary interventions investigated use of a supplement ( n  = 66 studies), which was predominantly caffeine ( n  = 49). Sleep interventions investigated sleep duration only, with the majority ( n  = 17) investigating the effect of partial sleep restriction under 5.5 h per night on dietary intake,  while three studies investigating total sleep deprivation. Conclusions: Investigating broader aspects of dietary such as overall diet quality and dietary patterns and other components of sleep health such as quality,   timing and sleep hygiene are important aspects for future research.